Kidney-Pancreas Transplant Recipients Experience Higher Risk of Complications Compared to the General Population after Undergoing Coronary Artery Bypass Grafting - Perdue, Jordyn M.; Ortiz, Alejandro C.; Parsikia, Afshin; Ortiz, Jorge (International Journal of Angiology, 2021)
This retrospective analysis aims to identify differences in surgical outcomes between pancreas and/or kidney transplant recipients compared with the general population undergoing coronary artery bypass grafting (CABG). Using Nationwide Inpatient Sample (NIS) data from 2005 to 2014, patients who underwent CABG were stratified by either no history of transplant, or history of pancreas and/or kidney transplant. Multivariate analysis was used to calculate odds ratio (OR) to evaluate in-hospital mortality, morbidity, length of stay (LOS), and total hospital charge in all centers. The analysis was performed for both nonemergency and emergency CABG. Overall, 2,678 KTx (kidney transplant alone), 184 PTx (pancreas transplant alone), 254 KPTx (kidney-pancreas transplant recipients), and 1,796,186 Non-Tx (nontransplant) met inclusion criteria. KPTx experienced higher complication rates compared with Non-Tx (78.3 vs. 47.8%, p < 0.01). Those with PTx incurred greater total hospital charge and LOS. On weighted multivariate analysis, KPTx was associated with an increased risk for developing any complication following CABG (OR 3.512, p < 0.01) and emergency CABG (3.707, p < 0.01). This risk was even higher at transplant centers (CABG OR 4.302, p < 0.01; emergency CABG OR 10.072, p < 0.001). KTx was associated with increased in-hospital mortality following emergency CABG, while PTx and KPTx had no mortality to analyze. KPTx experienced a significantly higher risk of complications compared with the general population after undergoing CABG, in both transplant and nontransplant centers. These outcomes should be considered when providing perioperative care.
Keywords: transplant; kidney; cardiovascular disease; cardiac surgery; coronary artery; risk factors; early